Himig ng kabataan a module on ukulele and rondalla playing for San Francisco High School Grade 7 Special Program in the Arts-Music - Basug, Arnida Faye; Timbol-Guadalupe, Jocelyn (Diliman, Quezon City U.P. College of Music, 2019)
At the end of the project, the Special Program in the Arts or SPA of the San Francisco High School (SFHS) is a program made to allow telented students enhance their potential in different aspects in arts. There are five different fields to choose from: Creative Writing in Filipino and English; Visual Arts; Theater Arts; Music; and Dance. The SPA music curriculum focuses on aspects such as: "Music as self-expressed in FIlipino tales, epics, rituals and festivals; music as a community resource in the ritual's tangible and intangible heritage of the people; music as continuing expression of the people's history and music as a global perspective in the contemporary times.
Thesis (B. M. Music Education) -- University of the Philippines, Diliman.
Keywords: School musicxInstruction and study -- Philippines; Ukulele -- Instruction and study; Rondalla -- Instruction and study